Integrated lipidomic and transcriptomic analyses identify altered nerve triglycerides in mouse models of prediabetes and type 2 diabetes - Phillipe D. O'Brien; Kai Guo; Stephanie A. Eid; Amy E. Rumora; Lucy M. Hinder; John M. Hayes; Faye E. Mendelson; Junguk Hur; Eva L. Feldman; Annemieke Aartsma-Rus; James Dowling; Maaike van Putten (The Company of Biologists, 2020)
Peripheral neuropathy (PN) is a complication of prediabetes and type 2 diabetes (T2D). Increasing evidence suggests that factors besides hyperglycaemia contribute to PN development, including dyslipidaemia. The objective of this study was to determine differential lipid classes and altered gene expression profiles in prediabetes and T2D mouse models in order to identify the dysregulated pathways in PN. Here, we used high-fat diet (HFD)-induced prediabetes and HFD/streptozotocin (STZ)-induced T2D mouse models that develop PN. These models were compared to HFD and HFD-STZ mice that were subjected to dietary reversal. Both untargeted and targeted lipidomic profiling, and gene expression profiling were performed on sciatic nerves. Lipidomic and transcriptomic profiles were then integrated using complex correlation analyses, and biological meaning was inferred from known lipid-gene interactions in the literature. We found an increase in triglycerides (TGs) containing saturated fatty acids. In parallel, transcriptomic analysis confirmed the dysregulation of lipid pathways. Integration of lipidomic and transcriptomic analyses identified an increase in diacylglycerol acyltransferase 2 (DGAT2), the enzyme required for the last and committed step in TG synthesis. Increased DGAT2 expression was present not only in the murine models but also in sural nerve biopsies from hyperlipidaemic diabetic patients with PN. Collectively, these findings support the hypothesis that abnormal nerve-lipid signalling is an important factor in peripheral nerve dysfunction in both prediabetes and T2D. This article has an associated First Person interview with the joint first authors of the paper.